Increased Hemoglobin Levels and Quality of Life in Menstruating Women Consuming Ajwa Date Palm (Phoenix dactylifera) Juice - Nurul Marfu'ah; Ratna Rahajeng Putri Yuwono; Nadia Iha Fatihah; Kartika Pibriyanti (Universitas Djuanda, 2025)
Anemia was prevalent among menstruating adolescent girls, affecting about 32% in Indonesia, and often reduced quality of life. Date palm juice contained carbohydrates, tryptophan, omega-3, vitamin C, vitamin B6, zinc, and magnesium, which could support hemoglobin improvement. This study aims to evaluate the potential of Ajwa date juice as an alternative therapy for women with menstrual anemia. An experimental design included five groups: Ajwa date palm juice (50% concentration) administered once daily (JKA1), twice daily (JKA2), or three times daily (JKA3); a positive control with a commercial anti-anemia product; and a negative control with mineral water. Treatments were given for five days to 25 respondents. Quality of life was assessed using a modified EQ-5D questionnaire, validated with the Pearson correlation test and tested for reliability with Cronbach’s alpha. Data were analyzed using one-way ANOVA at a 95% significance level. Results showed the greatest hemoglobin increase in the JKA3 group (mean 2.2 g/dL) and the smallest in JKA1 (1.4 g/dL), with no significant differences between groups (p > 0.05). Quality-of-life improvement was achieved fastest in JKA3 (2.4 days), followed by JKA2 and JKA1 (2.8 days each), also without significant differences (p > 0.05). In conclusion, Ajwa date palm juice improved hemoglobin levels and quality of life in anemic respondents. The three-times-daily regimen showed the most benefit, although statistical significance was not observed.